The effect of 2% chlorhexidine iontophoresis on dentin sealing ability of etch-and-rinse adhesive: An in vitro study - Kanittha Kijsamanmith; Panisara Srisatayasatien; Nichapa Thanindratarn; Chanisa Vichainarong; Jirapat Panyasukum (Elsevier, 2024)
Background/purpose: Iontophoresis could enhance the delivery of chlorhexidine into oral tissue. This study aimed to determine the effect of 2% chlorhexidine iontophoresis (CHI) on the sealing ability of etch-and-rinse adhesive in human dentin using hydraulic conductance (HD) measurement, scanning electron microscopy and energy dispersive x-ray spectroscopy (SEM-EDS). Materials and methods: Thirty-nine sound dentin specimens were prepared from 39 extracted intact third molars. Thirty specimens were used for HD measurement and randomly divided into 3 equal-sized groups; (1) No chlorhexidine treatment (control), (2) passive chlorhexidine treatment (CHT) and (3) CHI on acid-etched dentin. Each dentin surface was treated with etch-and-rinse adhesive. HD of each specimen was measured before treatment, after immediate bonding and after 14 days. The other 9 specimens were subjected to SEM-EDS analysis of the acid-etched dentin and the dentin treated with CHT and CHI. ANOVA test and Student-Newman-Keuls method were used for statistical analysis. Results: After bonding, there was no significant difference in percentage decrease of HD among the treatment groups (P > 0.05). After 14 days, CHI and CHT groups had greater percentage decrease of HD than the control (P < 0.001 and P = 0.009, respectively). Under SEM-EDS analysis, acid-etched dentin with CHI presented opened dentinal tubule orifices and more chlorhexidine precipitates on dentin than the dentin with CHT, which strongly related to a higher percentage of chloride ions on the CHI dentin surface (P < 0.001). Conclusion: The use of CHI on acid-etched dentin had a positive effect on dentin sealing ability of etch-and-rinse adhesive.